A Critical Humanist Intervention: Agency, Structure and Values - Vanesa Amaris (International Journal of Science and Society, 2021)
The main aim of the article is to suggest what and how a contemporary, revised version of humanism, inflected with critical realism and Marxism, can contribute to sociology. I focus primarily on two areas in which sociology is often found lacking today: theorizing the relationship between structure and agency, and deciding what to do with moral evaluations in sociological analyses. I argue that the solution to both lies in attempting to finally transcend the traditionally hostile and mutually exclusive paradigms of “humanist” or “cultural” Marxism on the one side and “anti-humanist” or “scientific” Marxism on the other. This enables us to carefully reinstate the agency of human subjects and the moral dimension, both of which were and still are dismissed by anti- or post-humanist social science, without neglecting the objective and causally relevant existence of social structures at the same time.